An increase of ammonia emissions from terrestrial ecosystems on the Tibetan Plateau since 1980 deduced from ice core record. (July 2020) - Zou, Xiang; Hou, Shugui; Zhang, Wangbin; Liu, Ke; Yu, Jinhai; Pang, Hongxi; Liu, Yaping
Abstract: Ammonia (NH3 ) emissions could have significant impacts on both ecosystems and human health. Ice cores from the Tibetan Plateau contain information about past ammonium (NH4 + ) deposition, which could yield important insights into historical NH3 emissions in the surrounding source regions as well as long-distance NH4 + aerosol transport via atmospheric circulation. In this paper, we present a high-resolution atmospheric NH4 + deposition record for the period, 1951–2008, reconstructed from the Zangser Kangri (ZK) ice core in the northern Tibetan Plateau. An empirical orthogonal function (EOF) analysis of major soluble ions (NH4 +, NO3 −, SO4 2−, Cl −, Na +, K +, Mg 2+ and Ca 2+ ) reveals that EOF 1 has significant loadings of all ions, therefore representing common transport pathways, while EOF 2 is only significantly loaded by NH4 + (0.86) and NO3 − (0.35), suggesting a unique signal possibly representing emissions from the surrounding terrestrial ecosystems on the Tibetan Plateau. Backward trajectory analysis indicates that the air masses over the ZK ice core drilling site primarily come from the northwestern Indian Peninsula. NH3 emissions from agricultural activities in this area likely contribute to the NH4 + deposition of the ZK ice core via the Indian monsoon. Correlations between EOF 2 time series and temperature, normalized difference vegetation index (NDVI) suggest that increasing temperature and vegetation after 1980 likely promoted NH3 emissions from terrestrial ecosystems. Our results provide a reliable and valuable assessment of NH4 + deposition from human activities and terrestrial ecosystems in the ZK ice core, and help in understanding air pollution over the past few decades in the northern Tibetan Plateau. Graphical abstract: Image 1 Highlights: For Zangser Kangri Glacier, ammonia comes from South Asia and nearby ecosystems. Ammonia emissions from ecosystems increased since 1980 on the Tibetan Plateau. Temperature affects ammonia emission from ecosystems on Tibetan Plateau. Abstract : Main findings of the work: An ice core NH4 + record shows an increase in ammonia emissions on the Tibetan Plateau since 1980, likely attributed to the restoration of regional terrestrial ecosystems.